The Birth of Sinology and the Contributions of Spain (Sinología hispánica. China Studies Review, 2024)
The term “Sinology” origins in the late 17th century and early 18th century. Since then, countless missionaries merged into China without prejudice, which not only brought “Eastward Spread of Western learning to China”, but also created “Westward Spread of Chinese culture to the world”, translating Chinese cultural classics to the west, which became the key to the birth of Sinology. Spain is a pioneering country with a thriving sinology study in Europe, and its contribution has greatly influenced the Western imagination of China and the birth of generations of sinologists. Due to different cultural backgrounds, cultural contexts, thinking patterns, people will have different conclusions and speak different truths about the culture. Sinology, which connects Chinese and international scholars to fulfill the mission of academic exploration in China studies. On the occasion of the 3rd International Conference (3-4, May, 2022) on China Studies: East West contact and dialogue organized by the Confucius Institute of León University, Professor Yan Chunde presented his keynote speech entitled “The Birth of Sinology and the Contributions of Spain”, aiming to summarize the history of sinology studies through translation of Chinese classics in different historical period of time and present Spanish sinologists’ contributions to the readers, concluding human beings need a variety of cultures to be inclusive to learn from each other's strengths, to make up for their own weaknesses, and finally to reach the cultural realm of "achieving unified goals of self and others-thus the world can be harmonized".